Ethnobotanical assessment of edible plant diversity in homegarden of Semarang District, Central Java, Indonesia (Asian Journal of Ethnobiology, 2025)
Abstract. Kusuma LA, Rahmadhani SE, Anam ZK, Nadhira S, Yasa A, Saensouk S, Setyawan AD. 2025. Ethnobotanical assessment of edible plant diversity in homegarden of Semarang District, Central Java, Indonesia. Asian J Ethnobiol 8: 116-139. This study aims to document and analyze the diversity, utilization patterns, and cultural importance of edible plants maintained in home gardens as a foundation for preserving local knowledge and supporting community-based biodiversity conservation. The research was conducted across three villages in Semarang District, Central Java, Indonesia, using semi-structured interviews with 120 respondents. A total of 64 plant species from 34 families were recorded. The findings reveal a dominance of herbs (46.88%) and shrubs (35.94%), with Zingiberaceae as the most represented family (12.5%). Plants were grouped into six main utilization categories: fruits (32.8%), spices (25%), vegetables and beverages (each 12.5%), medicines (12.5%), and staple foods (4.7%). The most frequently used parts were fruits (51.6%) and leaves (21.9%), followed by tubers, stems, seeds, flowers, and rhizomes. Key species such as Zingiber officinale, Syzygium polyanthum, and Aloe barbadensis showed high cultural significance, indicated by their Use Value (UV) of 0.03 each, Relative Frequency of Citation (RFC) values of 0.15, 0.14, and 0.13 respectively, and Index of Cultural Significance (ICS) scores of 112, 66, and 33. The Informant Consensus Factor (ICF) values were highest in the spice (0.71) and medicinal (0.65) categories, reflecting strong agreement among respondents regarding their ethnobotanical roles. Women, particularly housewives (35.83%), played a central role in selecting, using, and transmitting knowledge about plants. Preparation methods such as raw consumption (46.9%) and boiling (18.8%) reflected traditional practices, while most plants were intentionally cultivated (89.1%), highlighting a strong culture of home-based plant management. Despite pressures from modernization and land-use change, the integration of traditional knowledge into daily household practices continues to support food security, health resilience, and cultural continuity. The study emphasizes the need for revitalization efforts and community-based conservation strategies to sustain this living ethnobotanical heritage. These findings highlight the importance of integrating traditional plant knowledge into local development and biodiversity policies to enhance food security, public health, and community resilience.
Keywords: Biodiversity, cultural significance, edible plants, home gardens, medicinal plants, traditional knowledge